A Cell Biologist’s Field Guide to Aurora Kinase Inhibitors - de Groot, Christian O.; Hsia, Judy E.; Anzola, John V.; Motamedi, Amir; Yoon, Michelle; Wong, Yao Liang; Jenkins, David; Lee, Hyun J.; Martinez, Mallory B.; Davis, Robert L.; Gahman, Timothy C.; Desai, Arshad; et al. (Frontiers in Oncology, 2015)
Aurora kinases are essential for cell division and are frequently misregulated in human cancers. Based on their potential as cancer therapeutics, a plethora of small molecule Aurora kinase inhibitors have been developed, with a subset having been adopted as tools in cell biology. Here, we fill a gap in the characterization of Aurora kinase inhibitors by using biochemical and cell-based assays to systematically profile a panel of 10 commercially available compounds with reported selectivity for Aurora A (MLN8054, MLN8237, MK-5108, MK-8745, Genentech Aurora Inhibitor 1), Aurora B (Hesperadin, ZM447439, AZD1152-HQPA, GSK1070916) or Aurora A/B (VX-680). We quantify the in vitro effect of each inhibitor on the activity of Aurora A alone, as well as Aurora A and Aurora B bound to fragments of their activators, TPX2 and INCENP, respectively. We also report kinome profiling results for a subset of these compounds to highlight potential off-target effects. In a cellular context, we demonstrate that immunofluorescence-based detection of LATS2 and histone H3 phospho-epitopes provides a facile and reliable means to assess potency and specificity of Aurora A versus Aurora B inhibition, and that G2 duration measured in a live imaging assay is a specific readout of Aurora A activity. Our analysis also highlights variation between HeLa, U2OS and hTERT-RPE1 cells that impacts selective Aurora A inhibition. For Aurora B, all 4 tested compounds exhibit excellent selectivity and do not significantly inhibit Aurora A at effective doses. For Aurora A, MK-5108 and MK-8745 are significantly more selective than the commonly used inhibitors MLN8054 and MLN8237. A crystal structure of an Aurora A/MK-5108 complex that we determined suggests the chemical basis for this higher specificity. Taken together, our quantitative biochemical and cell-based analyses indicate that AZD1152-HQPA and MK-8745 are the best current tools for selectively inhibiting Aurora B and Aurora A, respectively. However, MK-8745 is not nearly as ideal as AZD1152-HQPA in that it requires high concentrations to achieve full inhibition in a cellular context, indicating a need for more potent Aurora A-selective inhibitors. We conclude with a set of “good practice” guidelines for the use of Aurora inhibitors in cell biology experiments.